A hybrid method based on artificial immune system and fuzzy k-NN algorithm for diagnosis of heart valve diseases - Sengur, Abdulkadir; Turkoglu, Ibrahim (Pergamon-Elsevier Science Ltd, 2008)
The use of artificial intelligence methods in medical analysis is increasiug. This is mainly because the effectiveness of classification and detection systems has improved ill a great deal to help medical experts in diagnosing. In this paper, we investigate the performance of an artificial immune system (AIS) based fuzzy k-NN algorithm to determine the heart valve disorders from the Doppler heart sounds. The proposed methodology is composed of three stages. The first stage is the pre-processing stage. The feature extraction is the second stage. During feature extraction stage, Wavelet transforms and short time Fourier transform were used. As next step, wavelet entropy was applied to these features. In the classification stage, AIS based fuzzy k-NN algorithm is used. To compute the correct classification rate of proposed methodology, a comparative study is realized by using a data set containing 215 samples. The validation of the proposed method is measured by using the sensitivity and specificity parameters. 95.9% sensitivity and 96% specificity rate was obtained. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: heart valve disease; artificial immune system; fuzzy k-NN classifier